Acid Lowering Agents and Trajectory of Vitamin B-12 Deficiency in the Boston Puerto Rican Health Study. (14th June 2022) - Dinesh, Deepika; Lee, Jong Soo; Scott, Tammy; Tucker, Katherine; Palacios, Natalia
Abstract: Objectives: Studies have reported an association between acid lowering agents (ALAs) such as proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2RAs) and malabsorption of vitamin B-12 (B-12). Therefore, we sought to examine the association between ALA use, including PPI and H2RA, and B-12 deficiency in a cohort of older Puerto Rican adults residing in the Boston MA metropolitan area. Methods: This analysis was conducted within the Boston Puerto Rican Health Study (BPRHS), an ongoing longitudinal cohort that enrolled 1502 self-identified Puerto Rican adults aged 45–75 y at baseline. Our study was comprised of 1428 participants at baseline, with complete baseline data on plasma B-12 concentration, of whom 1155 and 647 participated in wave-2 (mean 2.2 y from baseline ± 0.61 y), and wave-3 (mean 6.2 y ± 0.98 y), collections, respectively. B-12 deficiency was defined as plasma cobalamin <148 pmol/L or methyl malonic acid (MMA) >271 nmol/L. Covariate-adjusted logistic regression was used to examine the association between overall ALA, PPI and H2RA use and B-12 deficiency at baseline and wave-3 (mean 6.2 y) as well as between long-term use (mean 6.2 y) and B-12 deficiency at 6.2 y of follow-up. Logistic mixed effects models were used to examine associations between baseline ALA, PPI and H2RA use and trajectory of B-12 deficiency over 6.2 y of follow-up. Analyses were further stratified for B-12 supplement use, based on food frequency questionnaire. Results: Of 1428 participants at baseline, 455 were ALA users, of which 361 were PPI, 112 H2RA and 18 concomitant users. In baseline cross-sectional analyses, including analyses stratified for B-12 supplement use, we did not observe an association between ALA, PPI, H2RA use and B-12 deficiency. We also did not observe an association between long-term ALA, PPI, H2RA use and B-12 deficiency at 6.2 y. Further, in trajectory analyses, we did not observe an association between baseline ALA, PPI, H2RA use and trajectory of B-12 deficiency from baseline through 6.2 y follow-up, including in analyses stratified for B-12 supplement use. Conclusions: In this study we did not observe an association between ALA, PPI, H2RA use and B-12 deficiency over wave-3 (6.2 y) follow-up. Larger studies with more detailed exposure information are needed to further examine these associations. Funding Sources: NIH.